Sensory acceptability of jackfruit (Artocarpus heterophyllus lam.) seed food spread / Aladin M. Ibrahim ... [et al.] - M. Ibrahim, Aladin; Magan, Melfritz A.; Perono, Quitels Whyn A.; Larroza, Frazzile Kaye (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
This study examined the sensory acceptability of jackfruit (Artocarpus heterophyllus Lam.) seed spread. It aimed to determine the sensory acceptability of each treatment in terms of color, texture, aroma, and taste. It analyzed the significant differences in sensory qualities among the experimental treatments as well as the significant differences between the experimental treatments and the control. This study used a completely randomized design composed of sixty (60) evaluators comprised of students, faculty, and staff of a culinary school and food production workers. The mean, Z-test, and analysis of variance were used to analyze the data. The results indicated that the experimental treatments received moderately acceptable ratings in terms of aroma, texture, color, and taste. The control treatment received acceptable ratings for texture, color, and taste, with a moderately acceptable rating for aroma. Overall, the experimental treatments were generally considered moderately acceptable, while the control treatment was rated as acceptable. The study also showed that there was a significant difference among the experimental treatments in terms of aroma, texture, color, and taste. Treatments 3 and 4 showed a consistent result that was considerably comparable to the control treatment.